Poetry and nature in Kant’s aesthetics: on why poetry is the highest of all the arts - Fumagalli, Laura (The University of Edinburgh, 2018)
This dissertation will explore some of the reasons why poetry is ranked as the highest of all the arts in Kant’s aesthetics and what is the relation between nature and poetry. The central thesis is that poetry is the most beautiful art because it is made of language. It will be shown that poetry possesses free beauty and that pure judgments of taste in poetry are possible. Besides, poetry is the only art that originates entirely from the genius, because it shares the same language of the understanding, which, alongside imagination, constitutes the genius. Finally, poetry is the only art in which aesthetic ideas are in full power and can be fully expressed. This happens because language is pushed to its limits and is freed from conceptual constraints.
Keywords: Kant; aesthetics; poetry; nature; language